Multi-phase nature of sintered vs. arc-melted CrxAlFeCoNi high entropy alloys - experimental and theoretical study - Nicholas Lavery (Journal of Alloys and Compounds, 2019)
High entropy CrxAlFeCoNi alloys with x = 0, 0.5, 1.0 and 1.5 were synthesized using arc-melting and sintering preparation techniques. Three crystal structures (fcc, bcc and σ) were observed using XRD technique, while EDX measurements showed the presence of up to three chemically different phases (FeCr-rich phase with fcc structure, AlNi-rich phase with bcc structure and Cr-rich phase with bcc and/or σ structures). The reasons for the observed phase coexistence were addressed to total energy electronic structure calculations using KKR-CPA method accounting for chemical disorder effects. Such theoretical analysis confirmed that the multi-phase system was energetically more favorable than the single-phase one. Furthermore, DSC measurements allowed to identify two phase transitions in melted samples, unlike sintered ones due to high-temperature nitrogen corrosion. This process turned out to be highly selective, resulting in the formation of the scales consisting of AlnNm–phases at the cost of total Al loss in the HEA alloy.